2010
DOI: 10.1038/clpt.2010.205
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alertness-Promoting Effects of a Novel Histamine Subtype-3 Receptor Inverse Agonist in Healthy Sleep-Deprived Male Volunteers

Abstract: The alertness-promoting effect of MK-0249 (10 or 50 mg), a histamine subtype-3 receptor (HRH3) inverse agonist (IA), was evaluated in the stimulant reference sleep deprivation model (SRSDM) using a double-blind, double-dummy, placebo- and modafinil- (200 mg) controlled, four-period crossover design in 24 healthy young men. The two primary hypotheses were related to sleep latency (first appearance of one epoch of stage 2, 3, or 4 or REM sleep, as detected using polysomnography (PSG)) at 8:00 AM on day 2. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…The aim of the study was to assess the acute wake promoting effects of MK 0249 using a sleep deprivation model in healthy male volunteers. The primary outcome variable of this study was sleep latency on the MWT, and these data have been reported elsewhere (Iannone et al 2010). Here we report data on the effects of MK-0249 and modafinil on the spectral composition of the EEG during the MWT, sleep structure during recovery sleep as well as effects on the spectral compostion of NREM and REM sleep.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the study was to assess the acute wake promoting effects of MK 0249 using a sleep deprivation model in healthy male volunteers. The primary outcome variable of this study was sleep latency on the MWT, and these data have been reported elsewhere (Iannone et al 2010). Here we report data on the effects of MK-0249 and modafinil on the spectral composition of the EEG during the MWT, sleep structure during recovery sleep as well as effects on the spectral compostion of NREM and REM sleep.…”
Section: Methodsmentioning
confidence: 99%
“…Here we report data on the effects of MK-0249 and modafinil on the spectral composition of the EEG during the MWT, sleep structure during recovery sleep as well as effects on the spectral compostion of NREM and REM sleep. Details of the protocol can be found in (Iannone et al 2010). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential role for H3 IAs is also advocated in obesity and ethanol addiction (7,12). In a study of sleep-deprived healthy male volunteers using the stimulant reference sleep deprivation model, a single 10-mg dose of MK-0249 was associated with alerting effects (13). In essential tremor, however, a recent human trial using MK-0249 did not find significant effects in tremor reduction even at high single dose doses of H3 IA administration (14).…”
mentioning
confidence: 96%